Development of Mind Mapping Media to Increase Learning Motivation Class VII A Students SMP Bahrul Maghfiroh - Arisma, Putri; Irawan, Listyo Yudha (Institut Agama Islam Negeri Ponorogo, 2025)
According to the findings of a pre-survey on social studies classes at SMP Bahrul Magfiroh class 7A, pupils in this problem exhibit very little enthusiasm to learn. This was discovered during the learning meeting when it was discovered that several pupils had skipped or failed to attend class. Additionally, based on the previous meeting, the researcher employed LKPD in the next one, which motivated students to participate enthusiastically in social studies classes. According to the description given, the purpose of this study is to determine whether students are interested in learning about various topics. To this end, Mind Mapping media will be used as a learning tool to boost students' enthusiasm for learning. Utilising the ADDIE approach (analysis, design, development, application, and evaluation), mind mapping learning materials are developed through the use of development research, often known as research and development (R&D). A proportion of 80% fell into the practicable group according to the media feasibility test conducted by media and material experts. According to the results of surveys given to 23 students in total, the presence of active and interactive learning materials influences 32.8% of student motivation. Thus, it can be said that using mapping media helps boost students' motivation to understand social studies material.